(untitled) (Research, Society and Development, 2021)
In the context of women’s health, one of the pathologies that most affects this population is cervical cancer, also called cervical cancer. For its prevention, there is the Pap smear, which must be done when the woman starts sexual activity. In Brazil, the Ministry of Health and INCA recommend that this screening should be carried out between 25 and 64 years of age, however there are divergences in the literature regarding the correlation of the age group and the appearance of injuries. Thus, the study aims to make a list of the lesions that appear on the cervix of the woman who is under 25 and over 64 years old. For this, a systematic review was carried out on the Virtual Health Library (VHL) platform for the last five years (2017 to 2021). As a result, they obtained 7 articles read in full, of which one can find consonance among all with regard to four thematic axes built for the discussion: Prevention and the role of the nurse in the light of Dorothea Orem, Correlation of the bands age with the lesions, Pap smear and Epidemiological profile of the pathology. It is concluded that the most addressed theme among national and international studies is the Papanicolaou Examination, with differences in the construction of public policies for the promotion and prevention of women’s health, as women outside the age recommended by Brazilian public agencies, presented cervical lesions.